Varicella Zoster Virus Vasculopathy: A treatable form of rapidly progressive multi-infarct dementia after 2 years’ duration - Silver, Brian (2012)
We describe an extraordinarily protracted case of varicella zoster virus (VZV) multifocal vasculopathy in a man who presented initially with ischemic optic neuropathy and then suffered 4 episodes of stroke manifesting as multi-infarct dementia over a 2-year period. Brain magnetic resonance imaging (MRI) and angiography (MRA) revealed cortical and subcortical infarctions as well as vasculitic occlusion and stenosis. The patient was treated with corticosteroids and later with cyclophosphamide. More than 2 years after the onset of neurological disease, two cerebrospinal fluid (CSF) examinations revealed the presence of anti-VZV IgG antibody with reduced serum-to-CSF ratios of anti-VZV IgG compared with ratios for total IgG and albumin, indicative of intrathecal synthesis of anti-VZV IgG. After definitive diagnosis, immunosuppressive drugs were discontinued and he was treated with intravenous acyclovir; both mental status and gait improved and no further episodes of neurological dysfunction ensued. The favorable outcome in this patient indicates that VZV vasculopathy can be treated successfully even after 26 months. VZV must be considered as a possible cause of neurological disease in any patient with idiopathic multifocal vasculopathy.